Induced neural stem cell differentiation on a drawn fiber scaffold-toward peripheral nerve regeneration - Keshavarz,M; Wales,DJ; Seichepine,F; Abdelaziz,MEMK; Kassanos,P; Li,Q; Temelkuran,B; Shen,H; Yang,G-Z (Biomedical Materials, 2020)
To achieve regeneration of long sections of damaged nerves, restoration methods such as direct suturing or autologous grafting can be inefficient. Solutions involving biohybrid implants, where neural stem cells are grown in vitro on an active support before implantation, have attracted attention. Using such an approach, combined with recent advancements in microfabrication technology, the chemical and physical environment of cells can be tailored in order to control their behaviors. Herein, a neural stem cell polycarbonate fiber scaffold, fabricated by 3D printing and thermal drawing, is presented. The combined effect of surface microstructure and chemical functionalization using poly--ornithine (PLO) and double-walled carbon nanotubes (DWCNTs) on the biocompatibility of the scaffold, induced differentiation of the neural stem cells (NSCs) and channeling of the neural cells was investigated. Upon treatment of the fiber scaffold with a suspension of DWCNTs in PLO (0.039 gL-1) and without recombinants a high degree of differentiation of NSCs into neuronal cells was confirmed by using nestin, galactocerebroside (GalC) and doublecortin (Dcx) immunoassays. These findings illuminate the potential use of this biohybrid approach for the realization of future nerve regenerative implants.